Large dams in Asia : contested environments between technological hydroscapes and social resistance - Nüsser, Marcus (Advances in Asian human-environmental research,, 2014)
This book explores the multi-dimensional asymmetries of scale, time, and directions in the large dam controversy with a regional focus on Asia, especially on India and China. Whereas the concept of large-scale transformation of fluvial environments into technological hydroscapes originated in the West, widespread construction of large dams started in the countries of the Global South in the period after decolonisation. Construction and operation of large dams are amongst the most prestigious but also most sensitive development issues, often accompanied by massive resistance of adversely affected people and civil society organisations. Based on the notion of a contested politicised environment, various case studies are analysed to identify the dominant narratives and imaginations that shape the large dams debate. This volume largely contains contributions related to several subprojects from within the Cluster of Excellence Asia and Europe in a Global Context: Shifting Asymmetries in Cultural Flows, based at Heidelberg University, with several expert contributions from external researchers.